ANALISIS PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. SURYA KARSA MEDIAFORMASINDO - Moedigdo Sigit Prakoso Moedigdo Sigit Prakoso; Iis Darningsih Iis Darningsih (LPPM Swadaya Institute of Business and Communication, 2023)
The problem of this research is how the influence of leadership style, work motivation, and job training on employee performance at PT Surya Karsa Mediaformasindo. So this study aims to examine and analyze the influence of leadership style, work motivation, and job training on employee performance both partially and simultaneously at PT Surya Karsa Mediaformasindo. The research method used is a survey method with a quantitative approach. The data was obtained by using an instrument in the form of a questionnaire. The research population consisted of 320 employees of PT Surya Karsa Mediaformasindo, 96 people were taken as a sample using a random sampling method. The collected data were processed and analyzed using descriptive statistics and inferential statistics. Hypothesis testing uses the t-test and F-test which were previously carried out by the classical test as a requirement for regression analysis. The regression equation obtained Y=5.003+0.320X1+0.468X2+0.172X3. The results of the study: 1) Leadership style has a significant effect on employee performance with a sig.0.00 value <0.05 and a t count value of 4.467>t table 1.990, 2) Work motivation has a significant effect on employee performance with a sig.0.00 value <0.05 and t count value 6.725 > t table 1.990, 3) Training has a significant effect on employee performance with a sig. value of 0.017<0.05 and t count value 2.421> t table 1.990. 4) Leadership style, work motivation, and training simultaneously have a significant effect on employee performance with a sig.0.00 value <0.05 and an F count of 64.768. The relationship between the independent and dependent variables with an r-value of 0.824 means that 82.4% has a strong relationship. Based on an Adjusted R Square of 0.668, it shows the influence of leadership style, work motivation, and training on performance variables of 66.80%, while the remaining 33.20% is influenced by other variables.